Analisa punca masalah kecacatan produk menggunakan alat kawalan kualiti berstatistik - Wasoh @ Mohamad Isa, Halim (2008)
Quality control is an integral part in process manufacturing product. Every player in manufacturing industries must give the big attention in quality product in order to gain competitiveness in the industries. Any product defect should be cared effectively using quality control tools in order to ensure it does not occur again and causing a big loss to the business. Along with growing of the computer technology, a web based system was developed to overcome the causes of the product defect in the plastic manufacturing industry. A computer system was developed using cause analysis tools such as scatter diagram, Pareto diagram and cause and effect diagram. These tools were appropriately applied because it used to discover the cause of the problem as suggested by American Society for Quality (ASQ). The system was followed Phased Development methodology based on System Development Life Cycle. This system was a web based system and developed using Preprocessor Hypertext (PHP) as a server side language and My Structured Query Language (MySQL) as a database manager and Adobe Dreamweaver CS3 as a script editor . The final output was the report of root cause for the defect product. Is used as an aid that will help the organization improve their quality efficiency and reduce scrap in their work.